If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 = 6 + -6n Solving -24 = 6 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. -24 + 6n = 6 + -6n + 6n Combine like terms: -6n + 6n = 0 -24 + 6n = 6 + 0 -24 + 6n = 6 Add '24' to each side of the equation. -24 + 24 + 6n = 6 + 24 Combine like terms: -24 + 24 = 0 0 + 6n = 6 + 24 6n = 6 + 24 Combine like terms: 6 + 24 = 30 6n = 30 Divide each side by '6'. n = 5 Simplifying n = 5
| -5(-2-3)-2= | | 5v=-80 | | 3+1.5x+4=4x-2.5 | | -2x-22=34-4x | | 3=5(y-2) | | -6-5x+x=34 | | (n/6)=-8 | | -16t^2+128t=2 | | 1/5c+4=-9 | | -2-m=13 | | 2(x+9)=5(x+1) | | 5x-1=20x-10 | | 2x-5(-4)=16 | | -44=-5+9y | | 6x/10=36/15 | | n-18=-29 | | x=14(24)/4 | | 110=-7+9t | | 2y-12-y=38 | | 3a-45=89+16a | | 2(52)/13=x | | 6.4(3)/2=x | | m/-5+6=30 | | 2(9+x)=5(x+1) | | 6(x+4)=x+24 | | 2(0)-5y=16 | | 14+3a=8a-3(n-4) | | 4x+8=6x+22 | | -4(2-3x)=7-2(x-2) | | 13x-3=5x+29 | | -2x+2=24 | | 4/5x+7=-9 |